Phylogeographic Analyses of the East Asian Endemic Genus Prinsepia and the Role of the East Asian Monsoon System in Shaping a North-South Divergence Pattern in China - Ma, Xiangguang; Wang, Zhiwei; Tian, Bin; Sun, Hang (Frontiers in Genetics, 2019)
Prinsepia Royle (Rosaceae) is a genus native to China and the Himalayan region. In order to explain its current fragmented distribution pattern and to compare the impact of relatively recent climate changes on the genetic structure of Prinsepia species in different regions of China, a total of 66 populations and 617 individuals of four species of Prinsepia were genotyped using three cpDNA markers. Meanwhile, phylogenetic reconstructions and divergence dating were conducted using the cpDNA haplotypes dataset and the nuclear ribosomal internal transcribed spacer (ITS) dataset, respectively. Ecological niche modelling (ENM) was performed to predict the potential distribution of each species of Prinsepia at present and during the Last Glacial Maximum. Both ITS and cpDNA gene trees support a north-south divergence of Prinsepia species in China. The divergence time of the northern and southern Clades was around the late Oligocene. Combining the present distribution of Prinsepia species and their habitats, we inferred that the transition to a monsoon climate system in East Asia during the late Oligocene created a humid forest vegetation zone from central to east China, which potentially gave rise to the north-south divergence of Prinsepia species. Both regional climates and allopatric divergence may have played an important role in the speciation of P. sinensis and P. uniflora. P. sinensis had the lowest genetic diversity and a putative northward post-glacial colonization. The distribution range of P. uniflora was also extremely sensitive to interglacial-glacial cycles. P. utilis from southwestern China preserved more haplotypes than P. sinensis and P. uniflora due to its multiple and isolated refugia.